Capsular Polysaccharide From Bacteroides fragilis Protects Against Ulcerative Colitis in an Undegraded Form - Lijun Zheng; Lijun Zheng; Meihua Luo; Gaobo Kuang; Yangyang Liu; Debao Liang; Haiqing Huang; Xiaomin Yi; Congfeng Wang; Ye Wang; Qiuling Xie; Fachao Zhi (Frontiers Media S.A., 2020)
The prominent human symbiont Bacteroides fragilis protects animals from intestinal diseases, such as ulcerative colitis, and its capsular polysaccharide plays a key role in reducing inflammation. B. fragilis strain ZY-312 was isolated from the feces of a healthy breast-fed infant, and the zwitterionic capsular polysaccharide zwitterionic polysaccharide, TP2, was extracted. In rats with 2,4-dinitrobenzenesulfonic acid (DNBS)-induced enteritis, TP2 at an optimal dose of 2.5 mg/kg could significantly alleviate enteritis and reduced the degree of intestinal adhesions, the intestinal ulcer area, and the incidence of ulcers in rats. To understand the underlying mechanism, TP2 was labeled with Fluorescein isothiocyanate and orally administered at a dose of 2.5 mg/kg in rats. TP2 was mainly distributed in the cecum and colorectum, but it was not detected in the blood and other organs except that a compound with a molecular weight greater than that of TP2-FITC was found in liver tissue. During the absorption, distribution, metabolism, and excretion, TP2 was indigestible. These results were further confirmed by investigation in the simulated gastric, intestinal fluid, and colonic fluid with fecal microbiota in vitro, where TP2 remained unaltered at different time points. Furthermore, flora composition was analyzed in simulated colonic fluid with TP2 added and it was found that TP2 increased the abundance of Faecalibacterium, Enterococcus romboutsia, and Ruminococcaceae, whereas the abundance of the phylum Proteobacteria represented by Sutterella, Desulfovibrio, and Enterobacteriaceae was decreased. However, the amount of short-chain fatty acids in the simulated colonic fluid was not changed by intestinal flora post-TP2 addition. In conclusion, these findings confirmed that TP2, a capsular polysaccharide of B. fragilis, protects against ulcerative colitis in an undegraded form.